Effects of Add-On Ultramicronized N-Palmitol Ethanol Amide in Patients Suffering of Migraine With Aura: A Pilot Study - Chirchiglia, Domenico; Cione, Erika; Caroleo, Maria C.; Wang, Minyan; Di Mizio, Giulio; Faedda, Noemi; Giacolini, Teodosio; Siviglia, Serena; Guidetti, Vincenzo; Gallelli, Luca (Frontiers in Neurology, 2018)
Background: Palmitoyl ethanol amide (PEA) is an endogenously produced substance showing anti-nociceptive effect through both receptor and non-receptor mediated effects at the level of different cellular and tissue sites. This study showed the results of a single blind study that was conducted to evaluate both the safety and the efficacy of ultramicronized PEA (umPEA; 1200 mg/day) for up 90 days in patients suffering of Migraine with Aura (MA) treated with NSAIDs. Methods: A total of 20 patients, 8 male (33-56-years, average 41.4±7.8) and 12 female (19-61-years, average 38.5±11.9) with MA were admitted to our observation and diagnosed according to ICHD-3 criteria, they received umPEA (1200 mg/day) in combination with NSAIDs for up to 90 days . They were revaluated at 30, 60 and 90 days after treatment. Results: umPEA administration induced a statistically significant and time dependent pain relief. In particular, these effects were evident at 60 days (male P=0.01189; female P=<0.01) and they lasted until the end of the study (male P=0.0066; female P=0.01473). Conclusion: Although further studies are needed, our findings indicate that in patients suffering of MA treatment with umPEA had good efficacy and safety which candidate this compound as a therapeutic tool in pain migraine management.